Circular Fixation, Endless Possibilities: Rebuilding a Shattered Tibia using the Ilizarov Technique - A Case Report - Avik Kumar Naskar; Saurabh Satyanarayan Kunwar; Meet Ajay Mehta; Loknath Bhowmick; Himanshu Pradeep Ganwir; Vikas Anandrao Atram (Journal of Orthopaedic Case Reports)
Introduction: Tibial fractures, particularly complex and open types, present significant challenges in orthopedic trauma care due to their risk of complications and prolonged recovery. The Ilizarov technique offers a reliable and minimally invasive solution for achieving stable fracture fixation, promoting osteogenesis, and enabling early mobilization. Case Report: A 27-year-old male sustained a Grade 1 compound comminuted fracture of the right tibia along with a proximal fibular fracture following a motorcycle accident. The patient was managed with an Ilizarov external fixator. The procedure provided stable fixation, facilitated bone regeneration, and supported early rehabilitation. The patient achieved full functional recovery and complete radiological union without complications. At 1-year follow-up, bone alignment and regeneration were excellent. Conclusion: The Ilizarov ring fixation technique is an effective and dependable method for managing high-energy tibial fractures. It enhances bone healing, and promotes early functional recovery, making it a valuable tool in complex fracture management.